Efektivitas pembelajaran sains dini berbasis konvensional dengan pembelajaran sains dini berbasis montessori pada siswa TK GKI wikj elshaday jayapura - Florida Doloksaribu; Paul Johan Kawatu; Irwandi Yogo Suaka; Arta Indah Pasaribu (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Early childhood science education is a crucial foundation for developing logical thinking skills and scientific curiosity. This study aims to compare the effectiveness of conventional science learning methods and the Montessori method in enhancing the understanding of simple science concepts among kindergarten students. The method used was a quasi-experiment with a pretest-posttest control group design. The research subjects were 30 students in Group B at GKI Wikj Elshaday Kindergarten, Jayapura, divided into an experimental class (Montessori-based science learning) and a control class (conventional science learning). The research instrument was a structured observation sheet to measure children's understanding of science concepts such as observation, classification, and prediction. The results showed a significant difference between the posttest scores of the experimental class and the control class. The class with Montessori-based learning demonstrated a higher increase in concept understanding compared to the conventional class. This finding indicates that the Montessori approach, which emphasizes independent exploration and concrete teaching aids, is more effective in facilitating early childhood science understanding at GKI Wikj Elshaday Kindergarten, Jayapura